Soil seed banks in tropical forest fragments with different disturbance histories in southeastern Brazil - Martins, Andreza Maria [UNESP]; Engel, Vera Lex [UNESP] (Elsevier, 2007)
Soil seed banks are considered an important mechanism for natural regeneration in tropical forest ecosystems. This paper investigated the soil seed bank in two semideciduous seasonal tropical forest fragments with different disturbance histories in Botucatu, southeastern Brazil. In each study site, 40 superficial soil samples (30 cm × 30 cm × 5 cm) were taken at the end of both the dry and rainy seasons. The seeds were estimated by the germination method. Average soil seed density was 588.6 and 800.3 seeds m-2, respectively, for site 1 (less disturbed) and site 2 (more disturbed). Seed density and diversity (H′) were significantly higher in site 2 in both seasons. Non-woody taxa predominated in both fragments, but pioneer tree species were better represented in the less disturbed forest. Both ecosystems have a potential for regeneration from soil seed banks, but this potential is higher in the less disturbed site. Low richness and density of pioneer tree species in the seed bank indicate that the ecosystem has lost its resilience. The seed bank is not as important in these ecosystems as in other forests. Results indicate that management strategies to restore these forests should take into account the possibility of recovering soil seed bank processes and dynamics. © 2007 Elsevier B.V. All rights reserved.
Keywords: Forest disturbance; Natural regeneration; Pioneer species; Soil seed bank; Tropical seasonal forest; Ecosystems; Seed; Soils; Wood; Forestry; disturbance; forest management; forest soil; germination; pioneer species; regeneration; seed bank; tropical forest; Seeds; Soil; Botucatu; Brazil; Sao Paulo [Brazil]; South America